POLITICAL AND LEGAL REASONS FOR THE ESTABLISHMENT OF THE “DURAND LINE” (Modern American Journal of Social Sciences and Humanities, 2025)
This article details the political and legal reasons that led to the formation of the “Durand line” – the border between Afghanistan and Pakistan. The article also discusses in detail the problems that arose as a result of the creation and installation of this line.